2002
DOI: 10.1109/68.986815
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs-based high-performance p-i-n photodiodes

Abstract: In this letter, we have designed, fabricated, and characterized high-speed and high-efficiency InGaAs-based p-i-n photodetectors with a resonant cavity enhanced structure. The devices were fabricated by a microwave-compatible process. By using a postprocess recess etch, we tuned the resonance wavelength from 1605 to 1558 nm while keeping the peak efficiencies above 60%. The maximum quantum efficiency was 66% at 1572 nm which was in good agreement with our theoretical calculations. The photodiode had a linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…High performance infrared RCE-PDs using AlGaAs and InGaAs material systems were previously reported [14] [15] [16]. Recently, Kishino et al have demonstrated the first UV RCE-PD with an AlGaN-based MSM PD, where they have reported resonant peaks around 360 nm [17].…”
Section: Introductionmentioning
confidence: 98%
“…High performance infrared RCE-PDs using AlGaAs and InGaAs material systems were previously reported [14] [15] [16]. Recently, Kishino et al have demonstrated the first UV RCE-PD with an AlGaN-based MSM PD, where they have reported resonant peaks around 360 nm [17].…”
Section: Introductionmentioning
confidence: 98%
“…14 -18 This technique can also be used to improve the efficiency performance of LT-GaAs-based photodetectors. Previously, we had demonstrated GaAs-based RCE Schottky-barrier internal photoemission photodetector operating at 1.3 m. 3 In this work we demonstrate LT-GaAs based RCE photodetectors with high-speed operation at 1.55 m.…”
mentioning
confidence: 94%
“…To overcome this limitation and to use GaAs-based detectors in the 1.3-1.6 m wavelength region, mainly two detector structures were offered: Schottky-barrier internal photo-emission photodetectors and low-temperature-grown GaAs ͑LT-GaAs͒-based photodetectors. 3,4 It was shown that LT-GaAs was able to absorb long-wavelength signals due to midgap defects or As precipitates. 5 Moreover, subpicosecond carrier trapping time in LT-GaAs was also demonstrated.…”
mentioning
confidence: 99%
“…Since the refractive index contrast for the InP lattice match InAlAs and InGaAs is low the RCE-PD requires elevated number of the high/low index layer pairs, the most noble example of such device is in Ref. [8]. Here an alternative heterostructure was proposed and fabricated [9].…”
Section: Photo-detectorsmentioning
confidence: 99%